Software as a Service : in Search of Business Value for SMEs in Poland - Zygała, Ryszard (Software as a Service : poszukiwanie wartości biznesowej dla mśp w Polsce, 2010)
Today SaaS solutions are significant subject of interest for both researchers and practitioners. With contemporary Internet technology it is possible to use software application delivered by any distant provider. The common SaaS adoption in small and medium-sized enterprises (SMEs) seems to be matter of time. SMEs in Poland are characterized by restricted investment capital, which could support their IT infrastructure. The main purpose of the paper is to discuss these comprehensive benefits which will enable to involve SaaS initiatives in Polish SMEs. Additionally, the paper presents the set of economic rules which clarify the importance of the cloud computing and related technologies for SMEs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 301-310
Keywords: cloud computing; software-as-a-service; small and medium-sized enterprises; economic rules for SaaS adoption